THE TOUCH METHOD IN ACQUISITION OF ADDITIONAL KNOWLEDGE (Conference Zone, 2022)
The research work is devoted to the acquisition of additional knowledge of students, using the standard mathematical method of touch in the quality management of the learning process in the acquisition of knowledge based on ergonomics.